A modular, plasmin-sensitive, clickable poly(ethylene glycol)-heparin-laminin microsphere system for establishing growth factor gradients in nerve guidance conduits. (December 2015) - Roam, Jacob L.; Yan, Ying; Nguyen, Peter K.; Kinstlinger, Ian S.; Leuchter, Michael K.; Hunter, Daniel A.; Wood, Matthew D.; Elbert, Donald L.
Abstract: Peripheral nerve regeneration is a complex problem that, despite many advancements and innovations, still has sub-optimal outcomes. Compared to biologically derived acellular nerve grafts and autografts, completely synthetic nerve guidance conduits (NGC), which allow for precise engineering of their properties, are promising but still far from optimal. We have developed an almost entirely synthetic NGC that allows control of soluble growth factor delivery kinetics, cell-initiated degradability and cell attachment. We have focused on the spatial patterning of glial-cell derived human neurotrophic factor (GDNF), which promotes motor axon extension. The base scaffolds consisted of heparin-containing poly(ethylene glycol) (PEG) microspheres. The modular microsphere format greatly simplifies the formation of concentration gradients of reversibly bound GDNF. To facilitate axon extension, we engineered the microspheres with tunable plasmin degradability. 'Click' cross-linking chemistries were also added to allow scaffold formation without risk of covalently coupling the growth factor to the scaffold. Cell adhesion was promoted by covalently bound laminin. GDNF that was released from these microspheres was confirmed to retain its activity. Graded scaffolds were formed inside silicone conduits using 3D-printed holders. The fully formed NGC's contained plasmin-degradable PEG/heparin scaffolds that developed linear gradients in reversibly bound GDNF. The NGC's were implanted into rats with severed sciatic nerves to confirm in vivo degradability and lack of a major foreign body response. The NGC's also promoted robust axonal regeneration into the conduit.